Confirmed presence of territorial groups of golden jackals (Canis aureus) in Slovenia - Miha Krofel (Natura Sloveniae)
The article presents the first confirmed records of territorial groups of the golden jackal (Canis aureus) in Slovenia. During the survey at Ljubljansko barje on 20th February 2009, we noted a response by two jackal groups to a broadcasted howling near the village of Bevke (UTM VM82, 288 m a.s.l.). Since we recorded no response at any other location, it seems that the number of territorial golden jackals at Ljubljansko barje is small. Further studies would be needed to determine whether the jackals have already established permanent territories also in other regions of Slovenia.